Effect of Li ions on structure and spectroscopic properties of NaY(WO4)2: Yb/Ho phosphor. Issue 15 (15th October 2020) - Zhang, Chaoyi; Wang, Xinyu; Li, Chun; Lin, Hai; Zeng, Fanming; Su, Zhongmin
Abstract: We demonstrate the preparation of NaY(WO4 )2 phosphor particles with 1 mol% Ho 3+ and various Yb 3+ and Li + via solid-state reaction. The X-ray diffraction and infrared absorption spectrum results show that Yb 3+ and Li + would shrink the crystal lattice owning to their much smaller ionic radius. However, the W–O bond has been altered by Li + due to its stronger polarizability, and thus enlarges the crystal lattice parameters when Li + concentration is relatively high. According to the scanning electron microscope images, the mean size of Li + doped samples distribute from 1.75 μm to 2.58 μm. The up-conversion properties are studied under 980 nm laser diode excitation. All samples demonstrate two typical emission peaks located around 544 nm and 660 nm, which are corresponding to the 5 S2 / 5 F4 → 5 I8 and 5 F5 → 5 I8 transitions in Ho 3+ . Pump power law coefficients infer that both 544 nm and 660 nm emissions involves two-photon processes. Additionally, doping of Li + would significantly increase the green and red emissions intensities, with maximum enhancement of 3.65-fold and 7.51-fold, respectively. From Judd-Ofelt theory, the increasing intensity at 544 nm might attribute to the tailoring of local symmetry around Ho 3+, thus enlarging Ω 2 value. For the 660 nm emission, some promoted non-radiative relaxation processes could account for its great enhancement. The prolonged fluorescence decay lifetimes would make their great enhancement well comprehended. The notable enhancement in red emission would move the color-coordinates from green region to yellow-green regions, thus making it a novel candidate for multi-color materials to be further investigated.